Bernardo Atxaga, Obabakoak - Harriet Hulme (Opticon1826, 2011)
In 1992, Bernardo Atxaga’s Obabakoak, a collection of short stories about a mythical village in the Basque Country, was translated into English, to great acclaim. Nearly twenty years later, in January 2011, the announcement of a ceasefire by Basque Separatist group ETA has led to a number of articles, each accompanied by a picture of three masked figures, fists raised, in front of a poster emblazoned with ETA’s motto, Bietan Jarrai (“Keep up on both”). While the ‘mythology’ of this image concentrates and accentuates elements of violence and hostility, Obabakoak offers a different perspective, one which encourages us, as readers, to look beyond the masks.